Exploring EFL Students’ Perceptions of Reading Habits in English Academic Reading: A Case of a Cambodian Private School - Piseth Sum; Sarin Sok; Sina Pang (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Reading is one of the most essential skills to open up a world of knowledge, comprehension, and amusement. Despite increasing global interest, there has been little research on reading habits and academic performance in Cambodia. This study examines the English as a Foreign Language (EFL) students’ perceptions of reading habits in English academic reading. The study employed a qualitative approach, in which seven participants were selected for interviews using 18 questions to explore their perceptions of reading practices. The findings revealed that the EFL students had positive perceptions of reading habits and self-reported that it helped them improve their English proficiency in general. Furthermore, it also highlighted the importance of reading habits in enhancing students’ English academic reading. However, it is pivotal for educators to provide guidance and support to their students in the process of reading practices to improve their English academic reading achievements. Future researchers are recommended to conduct a study that comprehensively investigates the association between reading habits and academic achievements, employing quantitative and/or mixed methods in multiple schools.